Michiel van Groesen, Amsterdam’s Atlantic: Print Culture and the Making of Dutch Brazil - Raymond, Joad (BMGN - Low Countries Historical Review, 2017)
This is a double-faceted book. First, it is a history of the news of and debate over, in oral exchanges and print media, the Dutch conquest of north-east Brazil. This has not been studied as intensively, Michiel van Groesen contends, as is justified by the quantity of news and the effect of that debate in politics. The book is also perforce a history of that conquest and retreat (which took place between 1624 and 1654), as a necessary complement to the account of the media, a story that will be unfamiliar to many.